Ethnobotany and the search for new drugs [ (Ciba Foundation symposiu, 1994)
A compilation of articles by prominent experts in their respective fields on compensation for and collaboration with indigenous people in regard to their knowledge and provision of rare plants which are used for some of the most potent drugs in Western medicine